Transformasi fragmen DNA salmonella ke dalam sel e.coli DH5-a - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Genomic DNA from Salmonella typhimarium ATCC 14028, cultured in a Luria broth for 24 hr at 37°C, was isolated from the cells using EDTA as a chelathing agent and SDS as a detergent and lysing agent. The amount of genomic DNA was then digested with each of three restriction endonucleases, i.e., EcoRI, HindlII, and BamHI for 4 hr at 37°C. A plasmid (pUC19) was used as a vector. Prior to use, the pUC19 plasmid was splited with one of the three restriction enzymes and dephosphorylated using a bacterial alkaline phosphatase. The genomic DNA was then ligated to the corresponding prediggested plasmid using a ligase at 15°C over night. Transformation of the DNA recombinant into E.coli DH5-a was successfully carried out using a heat shock method as indicated by gel electrophoresis